(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
INTRODUCTION: Adolescent pregnancy poses serious challenges to public health, especially in developing nations. However, despite the significant adverse outcomes associated with early pregnancy, there exists a dearth of studies investigating the extent of knowledge and perspective of adolescent pregnancy among teenage girls. Therefore, this study aimed to assess the awareness and attitude of teenage girl students about adolescent pregnancy. MATERIALS AND METHODS: A cross-sectional descriptive study design was employed using simple random sampling of 145 adolescent girls in a public school located in Pokhara, Nepal. Data were collected using a self-administered questionnaire consisting of socio-demographic information, level of awareness and attitudes towards adolescent pregnancy. Descriptive and inferential analysis were conducted using SPSS version 21.0. RESULTS: More than half, 81 (55.9%), showed a moderate level of knowledge about adolescent pregnancy. Similarly, a statistically significant relationship was revealed between the level of awareness and sociodemographic variables, including ethnicity (p = 0.003), and family income (p = 0.006). Likewise, the results indicated that a significant proportion of the participants 117 (80.7%) had favourable attitudes towards adolescent pregnancy. In addition, statistical significance was demonstrated in the relationship between religion (p = 0.005), ethnicity (p = 0.007), and grade level (p = 0.001) and the level of attitude towards adolescent pregnancy. CONCLUSION: The study posits that the majority of adolescents had a favourable attitude towards adolescent pregnancy. However, there is still a misconception in their overall knowledge and attitude towards adolescent pregnancy. The study, therefore, emphasized the need to implement awareness programs on adolescent pregnancy within educational institutions and the broader society.